Proses Kreasi Seni Tari sebagai Ekspresi Diri Anak SD Negeri Wotan 02 Desa Wotan Kabupaten Pati - Asih Riyanti; Much. Arsyad Fardani; Nur Fajrie (ISLAMIKA, 2023)
This research is motivated by teachers and children in SD Negeri Wotan 02 in extracurricular activities, namely dance. The purpose of this study was to find out the processes and results involved in dancing activities for children at SD Negeri Wotan 02. This study used a qualitative research type with narrative analysis. The location of this research is at SD Negeri Wotan 02, precisely in Wotan Village, Dukuh Karanganyar, Sukolilo District, Pati Regency. The primary data sources are teachers and children participating in dance activities at SD Negeri Wotan 02. Secondary data sources come from research documentation, field notes and other supports. Data collection techniques used in this study were observation, interviews and documentation. Data analysis used in this study consisted of data reduction, data presentation, and inference. Based on the results of the research and discussion conducted, it can be concluded that the children's dance activities at SD Negeri Wotan 02 can be further improved. This is because in the process of dance activities many children do not master the basic movements so that the elements in dance with the creativity of children can develop creative dance arts.